Effect of profitability and liquidity on dividend Policy (Empirical Study of Agricultural Sector Companies in the Indonesia Stock Exchange 2014-2017) - Dede Pramurza; Devi Saputra (Journal of Applied Accounting And Business, 2019)
This research aims to find out the effect of profitability and liquidity to dividend policy. Dividend policy if related to company value becomes important because it has conflicting consequences. The object of this research are agriculture sector companies on Indonesian Stock Exchange in 2014 – 2017. Sampling in this research used purpossive sampling. Financial measurement used ROA, ROE, CR, and DPR. Data processed by SPSS 20. There is a simultaneous significant influence between Return On Assets (ROA), Return On Equity (ROE) and Current Ratio (CR) to Dividend Payout Ratio (DPR) of agricultural sector companies in the Indonesia Stock Exchange in 2014 - 2017.